Ethnic conflicts and minority rights - Narang, A.S. (2002)
The promotion of minority identity requires special measures intended to facilitate the maintenance, reproduction and further development of the culture of minorities. The issue is not one of conflicts between rights or of discrimination, but of generating confidence among minorities about the protection of their identity. - Reproduced.
Keywords: Ethnic conflicts; Minority groups